URBAN SUSTAINABILITY TRANSFORMATIVE EFFECTS OF GREEN ENERGY INFRASTRUCTURAL TECHNOLOGIES IN THE AFRICAN CONTINENT - Trynos GUMBO; Bonolo LETLAPE (Journal of Construction Project Management and Innovation)
The African continent just like others has joined a band wagon in the adoption and use of technologies that promote the production of green energy. Among the renewable energy infrastructure technologies worth noting is the landfill-gas to electricity investments that have been embraced by a few African countries since the advent of the new millennium. The technologies have been adopted not only to improve economic performances of the African continent but also to realise social and environmental benefits that accrue from the innovations. This article assesses the urban sustainability benefits that have been realised in South Africa and Cote D’lvoire as a result of the transformations that have taken place in green energy infrastructural technologies. Specifically, the study applies case study research designs and mixed method approaches to understand the socio-economic and environmental benefits that have been realised through the adoption and application of landfill gas to electricity generation and supply infrastructural technologies in two cities of eThekwini (South Africa) and Bingerville (Cote D’lvoire). Interviews, photographic surveys and focus group discussions helped to reveal that innovative projects have resulted not only in improved municipal solid waste management but more importantly urban environmental conservation, social and economic and improvements particularly of the urban and impoverished families that participate in the projects. To this end, the paper recommends the adoption and scaling up of innovative infrastructural technologies in renewable energy projects. Lessons that are being learnt from the best practices need to be replicated in other African countries and similar projects need to be encouraged, initiated and supported.